Experimenting on the metaverse to foster innovation - Cristina Mele; Tiziana Russo Spena; Stefano Paolo Russo (Spanish Journal of Marketing-ESIC)
Purpose – This study aims to investigate the evolving concept of the metaverse and its implications for service innovation. It seeks to understand how integrating technologies such as extended reality, blockchain, artificial intelligence and non-fungible tokens enables companies to experiment and innovate. Design/methodology/approach – Adopting a qualitative methodology, this investigation conducts an immersive netnography across more than 25 case studies spanning diverse industries such as gaming, retail, health care and education. The thematic analysis method is used to distill critical insights, providing a deep dive into the technological enablers, innovation processes and market adaptations within the metaverse. Findings – The study addresses four main building blocks through which companies experiment with the metaverse to foster innovation: enabling virtual identities’ agency, developing non-fungible tokens, designing immersive paths and crafting phygital microworlds. They shape the metaverse by enacting actors, resources, processes and phygital ecosystems. Companies obtain learning outcomes from such experimentation and identify learning challenges. Originality/value – This research contributes to the nascent body of knowledge on the metaverse and service innovation by providing a comprehensive framework that encapsulates the multifaceted ways companies experiment within the metaverse. It extends the understanding of digital-physical convergence in service research, offering theoretical and practical insights into the development of phygital service ecosystems. Experimentando en el metaverso para fomentar la innovación Objetivo – Este estudio tiene como objetivo investigar el concepto en evolución del Metaverso y sus implicaciones para la innovación en servicios. Busca comprender cómo la integración de tecnologías como la realidad extendida, la cadena de bloques, la inteligencia artificial y los tokens no fungibles permite a las empresas experimentar e innovar. Diseño/metodología/aproximación – Adoptando una metodología cualitativa, esta investigación realiza una netnografía inmersiva a través de más de 25 estudios de casos que abarcan diversas industrias como los juegos, el comercio minorista, la atención médica y la educación. Se emplea el método de análisis temático para destilar conocimientos críticos, brindando un profundo análisis de los habilitadores tecnológicos, los procesos de innovación y las adaptaciones al mercado dentro del Metaverso. Resultados – El estudio aborda cuatro bloques principales a través de los cuales las empresas experimentan con el Metaverso para fomentar la innovación: habilitar la agencia de identidades virtuales, desarrollar tokens no fungibles, diseñar senderos inmersivos y crear micromundos físico-digitales. Estos dan forma al Metaverso mediante la actuación de actores, recursos, procesos y ecosistemas físico-digitales. Las empresas obtienen resultados de aprendizaje de dicha experimentación e identifican desafíos de aprendizaje. Originalidad – Esta investigación contribuye al cuerpo de conocimiento incipiente sobre el Metaverso y la innovación en servicios al proporcionar un marco integral que encapsula las diversas formas en que las empresas experimentan dentro del Metaverso. Amplía la comprensión de la convergencia digital-física en la investigación de servicios, ofreciendo ideas teóricas y prácticas sobre el desarrollo de ecosistemas de servicios físico-digitales. 在元宇宙中进行实验以促进创新 目的 – 这项研究旨在探讨元宇宙概念的演变以及其对服务创新的影响。其目标在于深入理解通过整合增强现实、区块链、人工智能以及非同质化代币等技术, 如何使企业得以进行实验和创新。 设计/方法/途径 – 本研究利用定性研究方法, 进行了一项沉浸式网络民族志调查, 涵盖了跨越游戏、零售、医疗保健和教育等多个行业的25多个案例。通过主题分析方法, 提炼出关键见解, 深入探讨了元宇宙内的技术驱动因素、创新过程和市场适应性。 结果 – 这项研究以四个主要方面为切入点, 探讨了企业在元宇宙中促进创新的方法：启用虚拟身份的代理、开发非同质化代币、设计沉浸式路径以及打造物理-数字微观世界。通过这些措施, 企业塑造了元宇宙, 涉及行动者、资源、过程和物理-数字生态系统的执行。在此类实验中, 企业积累了丰富的学习经验, 并面临了 原创性 – 本研究旨在建立一个全面的框架, 以拓展关于元宇宙和服务创新的新知识, 揭示企业在元宇宙中进行实验的多方面方式。它不仅扩展了服务研究领域中数字与物理融合的理解, 还提供了有关发展物理-数字服务生态系统的理论和实践见解。